Reforestation regulated soil bacterial community structure along vertical profiles in the Loess Plateau - Wu, Fan; Wang, Yunqiang; Sun, Hui; Zhou, Jingxiong; Li, Ruijie (Frontiers in Microbiology, 2023)
Reforestation is a widely-used strategy for ecological restoration in areas facing ecological degradation. Soil bacteria regulate many functional processes in terrestrial ecosystems, however, how they response to reforestation processes in surface and deep soils remained unclear. Here, we selected artificial Robinia pseudoacacia plantation with different stand ages (8, 22, and 32 years) in a typical fallow forest on the Loess Plateau to explore the differential response of soil bacterial community to reforestation in different soil depth (surface 0-200 cm, middle 200-500 cm, deep 500-100cm). Results showed that alpha diversity and the presence of biomarkers (keynote species) decreased with the increasing soil depth, with a sharp reduce in family-level biomarkers number in 500-1000 cm depth, while reforestation had a positive impact on bacterial alpha diversity and biomarkers. Reforestation induced a more loosely connected bacterial community, as evidenced by an increase of 9.38%, 22.87%, and 37.26% in the average path length of co-occurrence network in all three soil layers, compared to farmland. In addition, reforestation reduced the hierarchy and complexity but increased the modularity of the co-occurrence network in top and deep soil layers. Reforestation also led to enrichment in relative abundance of functional pathways in all soil layers. This study sheds light on the strategies employed by deep soil bacteria in response to reforestation and underscores the significant potential of deep soil bacteria in terrestrial ecosystems, particularly in the context of human-induced environmental changes.